Pengaruh Media Pembelajaran Monopoli Terhadap Hasil Belajar PPKn Siswa Materi Pahlawanku Kelas IV SD Negeri Maulafa Kota Kupang - Elagetrida Seri; Kristina E. Noya Nahak; Heryon Bernard Mbuik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Monopoly learning media plays a crucial role in learning activities. It is hoped that teachers and students at Maulafa Elementary School in Kupang City can utilize this Monopoly learning media to enhance their knowledge and enhance their learning outcomes in the Civics (PPKn) subject, "My Heroes." The purpose of this study was to determine the effect of using Monopoly learning media on students' PPKn learning outcomes in the "My Heroes" subject. This study employed a quantitative approach with a pre-experimental design. This experimental design employed a one-group pre-test post-test pattern. Data collection techniques included observation, testing, and documentation, with 30 students participating. The instrument testing phase included validation, reliability, item difficulty, and item discrimination. Data analysis techniques used to test the average were normality, homogeneity, and t-test. The analysis results showed a significant difference between students' pretest and posttest scores after the treatment. The average pretest and posttest scores showed a difference of -33.167 with a standard deviation of 9.105. The t-value was -19.952 with 29 degrees of freedom (df) and a significance level (p) of 0.000 (p < 0.05). The conclusion is that there is a significant influence between monopoly learning media and student learning outcomes. This is proven by the results of the hypothesis using a paired sample test with a significance level of 0.05. The results showed a significance value (2-tailed) of 0.000 < 0.05, thus it can be concluded that H0 is rejected and Ha is accepted. Thus, there is a significant influence on learning outcomes using monopoly media in PPKn learning on the topic of "My Heroes" for fourth-grade students of Maulafa Elementary School, Kupang City.